Imitation model of destruction of aviation fibrous polymeric composite materials - Синеглазов, В. М.; Клюс, В. В. (Proceedings of National Aviation University (archive), 2000)
Considered are models imitating influence of lighting on dielectric construction materials with elements of lighting protection. Described are models of current spreading in multilayer materials and thermal destruction of fibrous polymeric composite materials caused by lighting current flowing on such materials